Efektivitas Terapi Rendam Kaki Air Hangat terhadap Perubahan Penurunan Tekanan Darah Ibu Hamil Preeklampsia - Maslahatul Inayah; Tri Anonim (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2021)
Maternal Mortality Rate (MMR) can be a measuring tool to determine the quality of health services both during pregnancy and postpartum. Pregnant women with preeclampsia can cause complications that lead to increased maternal mortality and perinatal mortality. There are several attempts to control high blood pressure. This method can use pharmacological or non pharmacological. The purpose of this study was to determine the effectiveness of warm water foot soak therapy on changes in blood pressure reduction of preeclamptic pregnant women. This type of research is a quantitative study with aresearch quasi-experimentaldesign, with adesign approach pre and post test in the intervention group and the conMtrol group. The sample for each group is 10 people, so that the total number of samples is 20 respondents.Bivariate analysis was performed using the Wilxocon test because the data distribution was not normal and the Mann-Whitney Test to determine the difference before and after the intervention was given.The results of the bivariate analysis showed that there was an effect of giving warm water foot soaking therapy to changes in the decrease in systolic and diastolic blood pressure of preeclamptic pregnant women with a value of p = 0.004 and p = 0.011 and there were differences in changes in the decrease in systolic and diastolic blood pressure between the intervention group and the control group. p = 0.001 and p = 0.007.